Effectiveness of Realistic Mathematics Education Approach on Problem-Solving Skills of Students - John Kirby L. Dinglasan; Danielle Rencell C. Caraan; Delon A. Ching (International Journal of Educational Management and Development Studies, 2023)
Mathematics is concerned with the method used in the teaching and learning process in addition to issues encountered in the cognitive domain. The Philippines’ education system is still dominated by traditional mathematics teaching, which frequently overlooks the goal of mathematics education—to prepare students to deal successfully with real-life situations. This affects the declining performance of the students in their overall mathematical ability, especially in problem-solving. Hence, this study utilized a pre-experimental design to measure the effectiveness of the Realistic Mathematics Education (RME) approach in the problem-solving skills of the students in terms of understanding the problem, devising a plan, carrying out the plan, and looking back. Furthermore, the cluster sampling technique was used in choosing thirty-five grade 9 students and evaluated their problem-solving ability using a pre-test and post-test assessments. Based on the result, there is a highly significant difference in the mean pre-test and post-test performance of the respondent before and after using the RME approach in all the four phases of problem-solving (p-value=0.000). This implies that the RME is an effective teaching approach that successfully improved the mathematical proficiency of the students, especially in all aspects of problem-solving skills. The findings verify that educators can use the RME approach to expose their students to more collaborative teaching-learning processes that incorporate real-world scenarios. Future researchers may also conduct a similar study in face-to-face learning to comprehensively use the RME approach.